PENGARUH THIN CAPITALIZATION, CAPITALINTENSITY, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Razif, Razif; Vidamaya, Rizq Al Aqibullah (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2017)
The purpose of this research was to analyze the influence of Thin Capitalization, Capital Intensity and Profitability to the Tax Avoidance either partially or simultaneously at manufacturing companies on the Indonesia Islamic Stock Index(ISSI) in the period 2013-2015. The data used in this research was a secondary data with 42 manufacturing companies used as the sample. The method of data analysis was Purposive sampling. The research data was accessed on www.idx.com of each company. The technique in analyzing the relationship between the independent and dependent variables was multiple linear regression. The result indicated that Thin Capitalizatgeion, Capital Intensity, and Profitability influenced on to the Tax Avoidance.